2020
DOI: 10.1097/md.0000000000022142
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes and pathways associated with subchondral bone in osteoarthritis via bioinformatic analysis

Abstract: Osteoarthritis (OA) is a high prevalent musculoskeletal problem, which can cause severe pain, constitute a huge social and economic burden, and seriously damage the quality of life. This study was intended to identify genetic characteristics of subchondral bone in patients with OA and to elucidate the potential molecular mechanisms involved. Data of gene expression profiles (GSE51588), which contained 40 OA samples and 10 normal samples, was obtained from the Gene Expression Omnibus (GEO). The raw data were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…KEGG enrichment analysis results showed that the 172 common DEGs were mainly involved in immune-related pathways, such as Rheumatoid arthritis, NF-kappaB signaling pathway, Osteoclast differentiation, TNF signaling pathway, MAPK signaling pathway, and T-cell receptor signaling pathway (Figure 1F; Table S3). These results were consistent with the previous results and demonstrated the aberrant expression of these genes lead to inflammatory response in OA synovitis tissues (42,43). On the other hands, we performed the clustering analysis of these DEGs for further clearly specific function using Metascape software (Figure 1G), and these genes mainly enriched and clustered eight categories, including inflammatory response, regulation of MAPK cascade, Pid Atf2 pathway, Thythmic process, response to extracellular stimulus, response to corticosteroid, multicellular organism process, and response to growth factor.…”
Section: Identification Of Degs and Functional Analysis Shows Oa Invo...supporting
confidence: 94%
“…KEGG enrichment analysis results showed that the 172 common DEGs were mainly involved in immune-related pathways, such as Rheumatoid arthritis, NF-kappaB signaling pathway, Osteoclast differentiation, TNF signaling pathway, MAPK signaling pathway, and T-cell receptor signaling pathway (Figure 1F; Table S3). These results were consistent with the previous results and demonstrated the aberrant expression of these genes lead to inflammatory response in OA synovitis tissues (42,43). On the other hands, we performed the clustering analysis of these DEGs for further clearly specific function using Metascape software (Figure 1G), and these genes mainly enriched and clustered eight categories, including inflammatory response, regulation of MAPK cascade, Pid Atf2 pathway, Thythmic process, response to extracellular stimulus, response to corticosteroid, multicellular organism process, and response to growth factor.…”
Section: Identification Of Degs and Functional Analysis Shows Oa Invo...supporting
confidence: 94%
“…The results of qPCR analysis showed that 9 upregulated genes, Pdzk1 , Vpreb1a , Cd72 , Igll1 , Tnfrsf19 , Gas6 , Zdhhc2 , Igfbp4 , and Hdac7, were significantly increased, and 10 downregulated genes, Dhcr24 , Padi4 , Gsr , Clec4d , Lilrb4a , Clec4e , Fcgr4 , Stfa2 , Olfm4 , and Cxcr1, were significantly decreased in Mx1;TβRI CA compared to the WT group ( Figure 4 A,B). The functions of these 19 DEGs are briefly described in Supplementary Tables S1 and S2 [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…45 Peptidoglycan recognition protein 1 (PGLYRP1) plays a role in innate immunity and has bacteriostatic activity. Yang et al 46 identified it work as a hub mRNA of the osteoarthritis subchondral bone. Our research shows that it is also a hub mRNA regulated by lncRNA in osteoporosis.…”
Section: Discussionmentioning
confidence: 99%